2019
DOI: 10.1111/2041-210x.13213
|View full text |Cite
|
Sign up to set email alerts
|

AviaNZ: A future‐proofed program for annotation and recognition of animal sounds in long‐time field recordings

Abstract: The routine collection of long‐time acoustic recordings of animals in the field presents new challenges in data analysis. While many terabytes of data are collected annually, effective use of this noisy, highly variable data require skilled humans to manually identify calls. While computer programs to automatically analyse these recordings are becoming available, it is important that they are user‐friendly and easy‐to‐use, so that everybody – citizen scientists, wildlife managers, researchers – can take advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
0
36
0
1
Order By: Relevance
“…Table describes software used for sound processing in the literature reviewed, but many other bioacoustics signal processing techniques are available. For instance, some recently released programs such as Acoular (Sarradj & Herold, 2017), warbleR (Araya‐Salas & Smith‐Vidaurre, 2017), and AviaNZ (Marsland, Priyadarshani, Juodakis, & Castro, 2019) were not used in the literature reviewed here, but we anticipate their use will be helpful for future practitioners of acoustic localization. For a more complete listing of sound processing techniques and software packages, see Priyadarshani, Marsland, & Castro (2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table describes software used for sound processing in the literature reviewed, but many other bioacoustics signal processing techniques are available. For instance, some recently released programs such as Acoular (Sarradj & Herold, 2017), warbleR (Araya‐Salas & Smith‐Vidaurre, 2017), and AviaNZ (Marsland, Priyadarshani, Juodakis, & Castro, 2019) were not used in the literature reviewed here, but we anticipate their use will be helpful for future practitioners of acoustic localization. For a more complete listing of sound processing techniques and software packages, see Priyadarshani, Marsland, & Castro (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing this detection method to manual review of a 2‐hr long recording, Ethier and Wilson (2019) found that the automated method successfully detected all manual annotations as well as picking up some detections that were too faint to be annotated by manual review. Automated methods are attractive due to their scalability to many hours of recording (Darras et al, 2019; Marsland et al, 2019), but calibration of these methods can be time‐consuming and may require expert knowledge (Priyadarshani, Marsland, et al, 2018). The number of detections generated by automated methods was as many as 2.7 million (Ethier & Wilson, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Data was processed in the AviaNZ software (Marsland et al, 2019). In the automated process, the software was first trained on a small amount of manually annotated data from the same location, collected in September 2018.…”
Section: Kiwi Survey Datamentioning
confidence: 99%
“…De manera simultánea y con el fin de alivianar la carga para las personas, se han perpetrado diversos esfuerzos alrededor del mundo por automatizar los procesos de detección y clasificación de señales acústicas (Aide et al, 2013;Ovaskainen et al, 2018;Sethi et al, 2020) . Entre estos esfuerzos podemos encontrar varios programas informáticos como ARBIMON-II (Sieve Analytics, 2015), AviaNZ (Marsland et al, 2019), monitoR (Katz et al, 2016) y warbleR (Araya-Salas & Smith-Vidaurre, 2018).…”
Section: Introductionunclassified